Predictors of electrolyte derangement among women with obstructed labor delivering from referral hospitals in rural western Uganda: a multicenter cross-sectional study - Elioba, John Luate Raimon; Ishimwe, Marie Pascaline Sabine; Kusolo, Isaac; Hakizimana, Theoneste (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Obstructed labor is regarded as one of the major causes of maternal morbidity and mortality, particularly in environments with minimal resources, including Uganda. We aimed to determining the prevalence and predictors of electrolyte derangement among women with obstructed labor delivering from Referral Hospitals in western Uganda. Methods: We conducted a cross-sectional study from labor suits of Hoima and Fortportal regional referral hospitals from May to August 2023. 295 mothers were consecutively recruited and structured questionnaire was used to get data used for analysis. Descriptive statistics followed by binary logistic regression were conducted to achieve the study objectives using Stata version 14.2. Results: Out of 295 respondents, 182 (62%) had electrolyte derangement. The most common pattern of electrolyte derangement was hyponatremia 138 (43%) followed by hypocalcaemia 67 (21%). Primary level of education (OR=0.4; 95%CI: 0.199-0.752; p=0.045), fasting in labor (OR=4.2; 95%CI: 2.281-7.996; p=<0.001) and herbal medicine use in labor (OR=4.3; 95%CI: 1.875-9.924, p=0.001) were independently associated with electrolyte derangement. Conclusions: The prevalence of electrolyte derangement was high compared to the reported national prevalence. Hyponatremia was the most common pattern of electrolyte derangement. Herbal medicine uses in labor, fasting during labor and maternal education were predictive for electrolyte derangement. There is a need for routine assessment of electrolytes in patients with obstructed labor. Attempts to correct hyponatremia should be made in a situation where electrolyte assessment cannot be done.